Genome Editing Fidelity in the Context of DNA Sequence and Chromatin Structure - Chechik, Lyuba; Martin, Ophelie; Soutoglou, Evi (Frontiers in Cell and Developmental Biology, 2020)
Genome editing by Clustered Regularly Inter Spaced Palindromic Repeat (CRISPR) associated (Cas) systems has revolutionized medical research and holds enormous promise for correcting genetic diseases. Understanding how these Cas nucleases work and induce mutations, as well as identifying factors that affect their efficiency and fidelity is key to developing this technology for therapeutic uses. Here, we discuss recent studies that reveal how DNA sequence and chromatin structure influences the different steps of genome editing. These studies also demonstrate that a deep understanding of the balance between error prone and error free DNA repair pathways is crucial for making genome editing a safe clinical tool, which does not induce further mutations to the genome.